CODE SWITCHING AND CODE MIXING IN STUDENT INTERACTIONS ON INSTAGRAM SOCIAL MEDIA - Almeida, Giena (JURNAL SELAKSA MAKNA, 2026)
This study aims to explain the phenomena of code-switching and code-mixing, as well as the underlying social factors in their use in interactions between students on Instagram. The approach used in this study is qualitative with a descriptive method. The data obtained came from students' writings that appeared in captions, comments, and direct messages on Instagram. Data collection was carried out through observation and recording techniques, then analyzed by categorizing information based on the type of code-switching and code-mixing and interpreted using a sociolinguistic approach. The findings show that students actively apply code-switching and code-mixing, especially between Indonesian, English, and regional languages. Code-switching is usually used to adjust to the context and interlocutor, while code-mixing functions as a strategy of expression and symbolism in digital communication. The social factors that influence its use include aspects of identity, social solidarity, modern image, and the characteristics of social media, which tend to be informal. This study highlights that code-switching and code-mixing in student interactions on Instagram are not merely linguistic phenomena, but also social practices that reflect the development of language and identity in the digital age. Penelitian ini bertujuan untuk menjelaskan fenomena code-switching dan code-mixing, serta faktor-faktor sosial yang mendasari penggunaannya dalam interaksi antara siswa di Instagram. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode deskriptif. Data yang diperoleh berasal dari tulisan siswa yang muncul dalam caption, komentar, dan pesan langsung di Instagram. Pengumpulan data dilakukan melalui teknik observasi dan pencatatan, kemudian dianalisis dengan mengkategorikan informasi berdasarkan jenis code-switching dan code-mixing, dan diinterpretasikan menggunakan pendekatan sosiolinguistik. Hasil penelitian menunjukkan bahwa siswa secara aktif menerapkan code-switching dan code-mixing, terutama antara bahasa Indonesia, Inggris, dan bahasa daerah. Code-switching biasanya digunakan untuk menyesuaikan diri dengan konteks dan lawan bicara, sementara code-mixing berfungsi sebagai strategi ekspresi dan simbolisme dalam komunikasi digital. Faktor-faktor sosial yang mempengaruhi penggunaannya meliputi aspek identitas, solidaritas sosial, citra modern, dan karakteristik media sosial yang cenderung informal. Studi ini menyoroti bahwa code-switching dan code-mixing dalam interaksi mahasiswa di Instagram bukan hanya fenomena linguistik, tetapi juga praktik sosial yang mencerminkan perkembangan bahasa dan identitas di era digital.